A Structured Cognitive Intervention Pathway as a decision-support tool for non-pharmacological interventions within a dementia care service (Innovative practice). (January 2021) - Carter, Mark; Quail, Zara; Bourke, Allison; Young, Charles
Individual cognitive interventions for Alzheimer's disease have been shown to be beneficial and cost effective when evaluated as sole interventions. However, there is a need for a systematic, person-centric, structured approach to guide non-pharmacological intervention selection based on disease stage, symptoms, outcome assessment, and individual requirements. Our Structured Cognitive Intervention Pathway aims to facilitate the selection of first-line, or subsequent, non-pharmacological management for people with Alzheimer's disease living at home and in elderly care facilities. We discuss the Pathway's conceptual basis and evaluation of implementation as a decision-support tool within a dementia care service in China.